Altered expression of the costimulatory molecules CD80, CD86, CD152, PD-1 and ICOS on T-cells from paracoccidioidomycosis patients: Lack of correlation with T-cell hyporesponsiveness - Cacere, Cami A. R.; Mendes-Giannini, Maria José Soares [UNESP]; Fontes, Cor J.; Kono, Adriana; Duarte, Alberto J. S.; Benard, Gil (Academic Press Inc. Elsevier B.V., 2008)
T-cell proliferative hypo responsiveness, a hallmark of paracoccidioidomycosis immune responses, underlies host's failure in controlling fungus spread, being reversible with antifungal treatment. The mechanisms leading to this hypoproliferation are not well known. Since costimulatory molecules have been shown to profoundly regulate T-cell immune responses, we investigated the hypothesis that the determinants of the responder versus tolerant state may be the regulated expression of, or signaling by, costimulatory molecules. Expression of CD80, CD86, CD28, CD152, ICOS and PD-1 costimulatory molecules were examined on T-cells and monocytes harvested from stimulated and unstimulated PBMC cultures of active paracoccidioidomycosis patients and healthy individuals cured of past paracoccidioidomycosis. Stimuli were gp43, the immunodominant component of Paracoccidioides brasiliensis, and a Candida antigen. While CD28 expression, critical for optimal T-cell activation, was comparable between patients and controls, CD152, PD-1 and ICOS, which preferentially deliver negative signaling, were overexpressed on patients' stimulated and unstimutated T-cells. PBMC cultures were carried out in presence of the respective blocking antibodies which, however, failed to restore T-cell proliferation. CD80 and CD86 were equally expressed on patients' and controls' monocytes, but overexpressed on patients' T-cells. Blockade with the respective blocking antibodies on day 4 of the culture also did not restore T-cell proliferation, while, on day 0, differentially inhibited Candida and gp43 responses, suggesting that different antigens require different costimulatory pathways for antigen presentation. Our data favors the hypothesis, raised from other foreign antigen models, that prolonged in vivo antigen exposure leads to an adaptive tolerance T-cell state which is hardly reverted in vitro. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Paracoccidioidomycosis; Costimulatory molecules; T lymphocyte; Adaptive tolerance; Anergy; Immunosuppression